2021
DOI: 10.2147/itt.s259126
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL-17 Agents in the Treatment of Axial Spondyloarthritis

Abstract: Axial spondyloarthritis (axSpA) describes a group of chronic inflammatory rheumatic diseases primarily involving the axial skeleton. IL-17 is involved in the pathogenesis of numerous inflammatory diseases, including inflammatory arthritis. Until a few years ago, the only biological agents licensed for the treatment of axSpA and nr-axSpA were TNF inhibitors. However, as some patients did not respond to TNF inhibition or experienced secondary failure, the introduction of the first two IL-17 inhibitors (secukinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 140 publications
0
7
0
1
Order By: Relevance
“…Axial spondyloarthritis (axSpA) is a chronic inflammatory disease characterised by inflammation and new bone formation in the sacroiliac joints and spine and include non-radiographic axSpA and radiographic axSpA (also known as ankylosing spondylitis (AS)) [ 1 , 2 , 3 ]. Treatment options for axSpA include non-steroidal anti-inflammatory drugs and biologic disease-modifying anti-rheumatic drugs (bDMARDs) that target tumour necrosis factor-alpha (TNFα) or interleukin (IL)-23/17 axes [ 4 , 5 , 6 , 7 , 8 ]. The efficacy of TNFα and IL-23/17 inhibitors in controlling signs and symptoms of axSpA has been shown in clinical trials [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Axial spondyloarthritis (axSpA) is a chronic inflammatory disease characterised by inflammation and new bone formation in the sacroiliac joints and spine and include non-radiographic axSpA and radiographic axSpA (also known as ankylosing spondylitis (AS)) [ 1 , 2 , 3 ]. Treatment options for axSpA include non-steroidal anti-inflammatory drugs and biologic disease-modifying anti-rheumatic drugs (bDMARDs) that target tumour necrosis factor-alpha (TNFα) or interleukin (IL)-23/17 axes [ 4 , 5 , 6 , 7 , 8 ]. The efficacy of TNFα and IL-23/17 inhibitors in controlling signs and symptoms of axSpA has been shown in clinical trials [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…AxPsA as a unique presentation is supported by differing responses among patients with axSpA to biological agents that target the IL-23/IL-17 axis. Despite the efficacy of IL-12/23 and IL-23 inhibitors in PsA [ 9 , 16 18 ] and the efficacy of IL-17 inhibitors in PsA and axSpA [ 37 , 38 ], a trial of an IL-23 inhibitor, risankizumab, in AS demonstrated negative results [ 39 ]. Additionally, cumulative evidence from three phase 3 placebo-controlled trials of patients with axSpA showed that patients treated with the anti-IL-12/23p40 monoclonal antibody ustekinumab did not achieve clinically meaningful improvement across key efficacy endpoints when compared with placebo [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in favor of the anti-inflammatory function of irisin, we also disclosed that serum irisin positively correlated with C-peptide, another molecule with similar beneficial effects on inflammation ( 40 ). Of note, a previous study performed in patients with type 2 diabetes mellitus reported an inverse association between irisin and interleukin (IL)-17A ( 41 ), one of the main pro-inflammatory cytokines implicated in the pathogenesis of axSpA ( 1 ). IL-17A was suggested to exert an indirect pro-atherosclerotic role in obese individuals ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Axial spondyloarthritis (axSpA) is a chronic inflammatory disease that mainly affects the axial skeleton (spine and pelvic joints), although its main symptoms can also be accompanied by extra-articular manifestations ( 1 ). axSpA has detrimental effects on the health status of the patients affected by this condition including, but not limited to, pain, stiffness and poor physical function ( 2 ).…”
Section: Introductionmentioning
confidence: 99%